PENGARUH SIMULATION-BASED LEARNING BERBASIS TEACHING AT THE RIGHT LEVEL (TaRL) TERHADAP KETERAMPILAN DASAR MENGAJAR MAHASISWA PRODI PGSD - Awalina Barokah; Bramianto Setiawan (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2026)
This study aimed to examine the effect of the Simulation-Based Learning (SBL) model integrated with the Teaching at the Right Level (TaRL) approach on the basic teaching skills of students in the Elementary School Teacher Education (PGSD) program. The study employed a quasi-experimental method using a nonequivalent control group design. The participants consisted of two classes: an experimental group receiving SBL integrated with TaRL and a control group receiving conventional instruction. Data were collected using an observation checklist assessing basic teaching skills, including lesson opening and closing, explaining, questioning, providing reinforcement, classroom management, guiding small-group discussions, and instructional variation. Data were analyzed using an independent samples t-test. The results revealed a significant difference between the experimental and control groups (p < 0.05). The experimental group achieved a higher mean score in basic teaching skills (87.95) than the control group (80.12). These findings indicate that the implementation of Simulation-Based Learning integrated with the Teaching at the Right Level approach has a positive effect on improving the basic teaching skills of prospective elementary school teachers.